2021
DOI: 10.2186/jpr.jpor_2019_391
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of keratinized mucosa on peri-implant tissue health using a multivariate analysis

Abstract: Maintaining peri-implant tissue health is necessary for the longterm success of implant treatment. Poor oral hygiene, smoking, and a history of periodontal disease have been reported as risk factors for peri-implantitis [1].Previous research has discussed whether the presence of keratinized mucosa (KM) is required to keep peri-implant tissue healthy [2].Peri-implant tissue health requires no clinical signs of inflammation, no bleeding and suppuration on gentle probing, no increase in probing depth compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…For ΔBLm, ΔBLd, and ΔBLb, KMW <1.5 mm was a significant factor for bone loss over time (Tables 3 and 4A). This result is consistent with the longitudinal study by Perussolo and colleagues 3 and the cross‐sectional studies by Shimomoto and colleagues 11 & Mameno and colleagues, 37 which mainly used multivariate analyses to evaluate PM implants. The studies suggested that KMW ≥2 mm was an important factor in bone loss.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…For ΔBLm, ΔBLd, and ΔBLb, KMW <1.5 mm was a significant factor for bone loss over time (Tables 3 and 4A). This result is consistent with the longitudinal study by Perussolo and colleagues 3 and the cross‐sectional studies by Shimomoto and colleagues 11 & Mameno and colleagues, 37 which mainly used multivariate analyses to evaluate PM implants. The studies suggested that KMW ≥2 mm was an important factor in bone loss.…”
Section: Discussionsupporting
confidence: 90%
“…A history of periodontitis 11,12 was recorded when medical records or patient inquiries indicated that the implant was placed at a site where tooth extraction occurred because of chronic periodontitis. The definition of periodontitis conformed to that reported by Papapanou and colleagues 13 …”
Section: Methodsmentioning
confidence: 99%
“…22 The results of a more recent clinical trial published by Shimomoto et al in 2021 also suggest that the width of keratinized tissue increases periimplant bone stability. 23 On the other hand, Roccuza et al, in their retrospective study published in 2015 with 10 years of follow-up, concluded that even if the width of the keratinized tissue is inadequate, this condition can be tolerated with good oral care. 24 According to the study of Kim et al in 2009, inadequate keratinized tissue width around the implant does not have a definite negative effect on poor oral hygiene and soft tissue health.…”
Section: Amount Of Keratinized Mucosamentioning
confidence: 99%